Age of Criminal Responsibility - Sulukhia, Lili (Journal of Law, 2024)
This article is dedicated to the age of criminal responsibility. The relevance of this topic is defined by studying the physical and mental nature of a child and taking into account the socio-economic factors affecting him/her, it is possible to identify the problematic nature of the age of criminal responsibility. The measure applied to a child committing a criminal act should be proportional to the severity and circumstances of the offense, as well as the conditions and requirements of the child considering his/her best interests.[1] Introducing this study, a reader will be convinced that children in conflict with the law should not be treated as adults because of their limited emotional, psychological, moral, and social development. [1] International Standards in the Field of Juvenile Justice, UNICEF, 2011, 35, adopted by UN resolution N40/33 of 29 November 1985.